Effects of different transplanting seedling ages and nitrogen managements on plant type of indica hybrid rice - Lü Tengfei; Zhou Wei; Sun Yongjian; Zhu Yi; Yan Fengjun; Yang Zhiyuan; Ma Jun (浙江大学学报. 农业与生命科学版)
Transplanting seedling age is an important factor that may greatly affect the population quality and grain yield formation of rice. Related researches have showed that by extending the transplanting seedling ages, the tillering growth rate would slowed down; the growth duration would get shorted; peak seedling stage would occur in advance; leaf area index (LAI) at full heading stage, the numbers of effective panicle per plant and grains per panicle would decreased, resulting in obvious reduction of grain yield. Due to the special landscape of the hilly area in China, the old transplanting seedling age still exist in those areas. The rice plant type is closely associated with the formation, growth and development of panicle, thus a good individual plant is essentially important for improving the quality of the population. Besides, nitrogen and its management are also important factors affecting the growth and grain yield formation of rice.To investigate the effect of seeding ages and nitrogen managements on some plant type characteristics of hybrid rice, F you 498 was used as test material in this experiment. Split plot was conducted with transplanting seedling ages (35 d, 50 d and 65 d) as main plot and nitrogen application strategy (0% panicle fertilizer, 20% panicle fertilizer, 40% panicle fertilizer and 60% panicle fertilizer) as sub-plot. The aims were to provide the theoretical and practical data for improving the grain yield of old transplanting seedling age in hilly areas.The results showed that the LAI at full heading stage decreased with the extension of seedling age, and the average LAI of 65 d seedling age was significantly lower than 35 d and 50 d, but due to the larger and wider of top 3 leaves of 65 d seedling age, its high effective leaf area ratio was significantly larger than that 35 d and 50 d. With the increase of nitrogen fertilizer application ratio at panicle differentiation stage, the LAI of 50 d and 65 d seedling age at full heading stage increased first and then decreased, and the LAI reached its maximum when the panicle fertilizer ratio was 40%. With the extension of seedling age, the length, width and angle of top 3 leaves increased gradually, and the specific leaf mass of 65 d seedling age was the largest, followed by 35 d and 50 d; the length of the 1st and 2nd leaves from top and the angle of top 3 leaves of 65 d seedling age were significantly higher than those of 35 d and 50 d, and its length of the 3rd leaf from top and the width of top 3 leaves were also higher than 35 d. The length, width, thickness and angle of top 3 leaves were positively correlated with the number of spikelets, filled grains and grain mass per panicle; and either extending the seedling age or decreasing base-tiller fertilizer ratio could reduce the plant height significantly. The effect of transplanting seedling ages on plant type of hybrid rice was closely related with earing fertilizer managements, and extending the transplanting seedling age or increasing the panicle fertilizer ratio could improve fertilizer tolerance and lodging resistance of F you 498, and applying more earing fertilizer under long seedling age could make rice have better population quality and strong photosynthetic capacity, while too large and loosely top leaves would reduce transmittance and photosynthetic efficiency of rice population, and making the yield of long seedling age hard to improve further.It is concluded that long seedling age of rice has large and thick leaves, and applying 40% total nitrogen fertilizer at panicle differentiation stage will be beneficial to expand leaf areas and increase the number of spikelets per panicle. But the oversize of upper leaves can lead to leaf drooping, lower leaves shading, thus will reduce the photosynthetic efficiency of rice groups after flowering, and decrease the setting percentage and 1 000-grain mass, causing production reduction. In addition, the extension of the transplanting seedling age and the reduction of the base-tiller nitrogen fertilizer application ratio can obviously reduce the plant height, improve the ability of resistance to lodging and improve plant type.